Development of QRAR/QSAR Method by Biopartioning Micellar Chromatography and Application in Prediction Toxicity of Bioactive Ingredients of Traditional Chinese Medicines - Liang, Y.; Ren, X.J.; Wang, S.R.; Wu, L.P.; Xue, J.T.; Wen, S.L.; Ye, L.M. (Asian Journal of Chemistry, 2012)
The knowledge of drug potential toxicity is great need for risk assessment and screening candidates of drugs in the drugs development. The use of biopartitioning micellar chromatography has proven to be valid in predicting several biological activities of different kinds of drugs in development new drugs. The use of quantitative retention-activity relationship/quantitative structure-activity relationship basing on biopartitioning micellar chromatography to estimate acute toxicity is an attractive alternative to experimental measurements. In this paper, a data set of 58 chemical drugs from various structure classes with median lethal dose (LD50) data available expressed as pLD50 in this paper was studied to construct acute toxicity model. The pLD50 was reciprocally correlated to the negative value of the capacity factor (-1/k). The correlation was better with the addition of molecular descriptors (R2 = 0.823). The method of quantitative retention-activity relationship/quantitative structure-activity relationship developed by construction model of chemical drugs was applied to predict toxicity of bioactive ingredients of traditional chinese medicines. The results showed that application was predictable and practical in bioactive ingredients of traditional Chinese medicines.